CRICKET PRODUCTION FORECASTING USING THE MOVING AVERAGE METHOD - Suseno, Pangki; Junianto, Dwi; Sukmana, Farid; Pamungkas, Bian Dwi (STKIP PGRI Tulungagung, 2024)
Cricket production in Indonesia has promising business potential, particularly in rural areas. However, production variability is often a major challenge for farmers to maintain economic stability. Therefore, production forecasting methods are needed for better management. This study aims to predict cricket production using Moving Average (MA) and Weighted Moving Average (WMA) methods and compare their accuracy. The research was conducted in Rejotangan District, Tulungagung, using 12 weeks of cricket production data from May to August 2024. The accuracy of the method was measured using Mean Absolute Deviation (MAD), Mean Squared Error (MSE) and Mean Absolute Percentage Error (MAPE). From this research, the best model that can be used to predict the amount of cricket production is the Weighted Moving Average (WMA) model with n = 4 with the lowest prediction accuracy value (MAD, MSE and MAPE) of 16.05, 514.513 and 10.985% respectively. From the forecasting results, the total production of crickets in the existing farm for one period ahead with the WMA model n = 4 is 150.9 kg.